Potensi Daya Tarik Wisata Alam Gunung Kapur Ciampea Sebagai Objek Wisata Edukasi Berkelanjutan di Kabupaten Bogor - Fitrianingsih; Siti Fadjarajani; Cahya Darmawan (Indonesian Journal of Glasial Geography, 2024)
The development of tourism has progressed, especially the tourist attraction presented to visitors, especially in educational tourism which is currently a tourism trend presented by managers so that visitors can interpret and get direct learning experiences so that educational tourism has the potential to develop tourist attractions in their area. One of the sustainable educational tours is the Ciampea Limestone Volcano tour, Bogor Regency, West Java which offers nature-based tourism. This study aims to determine the potential of the natural tourism attraction of Mount Kapur Ciampea as a sustainable educational tourism object by using a descriptive qualitative approach, SWOT analysis method (Strenghts, Weaknesses, Opportunities, Treats) with data obtained based on literature review and documentation studies. The results of this study are that Mount Kapur tourist destinations have the potential for sustainability educational tourism including: 1) Nature-based tourism in the form of roti stone peaks, lalana peaks, galau peaks, and cave expeditions, 2) there is an endemic long-tailed monkey (macaca fascicularis), 3) there is an information center at the location of Mount Kapur Ciampea, 4) there is direction from the manager regarding tracking routes and camping areas, 5) access to the general force is easy to find.